‘Badan Penyelenggara Jaminan Sosial Ketenagakerjaan’ in the Perspective of Welfare State - Lestari, Tri Suci; Irmayani, Tengku (Talenta Publisher, 2024)
The Social Security Agency for Employment as social protection insurance for all workers in Indonesia has five main products. Each BPJS employment product has benefits and advantages for its participants. This research method is qualitative, namely by describing and analyzing data that has been obtained through data collection techniques of interviews, and literature study which is then explained in the form of detailed and systematic explanations. The results of this research show that based on the country typology formulated by Titmus, following the benefits facilitation provided by BPJS employment. The first point is realized with death benefits, work accident benefits, and old age benefits which provide protection benefits to workers when they can´t carry out work when sick, providing compensation and scholarships to families who have lost their source of livelihood, and several other benefits.